The Role of Human Capital and Lecturer Career Motivation in Career Success - Sari, Anita Kartika; Usman, Indrianawati; Yulianti, Praptini (Migration Letters, 2024)
This quantitative study seeks to deepen understanding of the complex relationship between human resources, career motivation, and career success among lecturers in Indonesia. In order to achieve this goal, this research used a survey via the Google Form platform with a 5-point Likert scale as a data collection method. The main focus of the research is on 400 lecturers who are members of the Higher Education Service Institutions (LLDIKTI) 1-16 in Indonesia. The research results analyzed using Partial Least Squares (PLS) Structural Equation Modeling revealed a strong and significant relationship between human resources and lecturer career achievements. Career motivation proved to be an important mediator in this relationship. These findings underscore the transformative role of human resource development in motivating lecturers to progress in their academic careers. This study differentiates itself from previous research that focuses more on the context of business organizations, by focusing on academic aspects. This research also validates subjective and objective aspects in assessing career achievement, providing new insights regarding the career development of lecturers in Indonesia. The results of this research provide a strong foundation for the development of better policy strategies to improve the welfare and career advancement of lecturers in the Indonesian higher education environment.